Analysis of Port-Based Discharge Water Treatment of Ships, Case Study: Terminal Petikemas Surabaya - Taufik Fajar Nugroho; Alam Baheramsyah; Nurkhairana Aryanti Trikurnia (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2019)
For 90% of world trade is carried by shipping industry. In Indonesia, highly concentrated goods movement are reported in Java and Sumatera which leads Tanjung Perak, Surabaya to become second largest ship terminal after Tanjung Priok, Jakarta. As the loading and unloading process is on call, any kinds of wastewater are continuously being discharged (sludge, oily sludge, blackwater and greywater). All wastewater if continuously discharged without any proper treatment is harmful to both human and aquatic environment. Especially in Indonesia and northern part of Java island where marine tourism is growing but in the other hand, also the home of largest ports. The purpose of this research is to design a fixed, compact discharge water treatment plant in one pilot international terminal, Terminal Petikemas Surabaya. The capacity of each discharge water receiver and treatment is determined according to ship’s arrival data. Based on the data analysis, the capacity of sludge receiver is 25 m3/day, oily bilge receiver for 200 m3/day, blackwater for 10 m3/day and greywater for 20 m3/day. Hereinafter, through the literature review of various kinds of wastewater treatment, a fixed and compact port-based discharge water treatment plant is designed by combining Membrane Bioreactor (MBR) for greywater, centrifugation for sludge, combination of ultrafiltration and reverse osmosis for oily bilge and Source Separation Sanitation (SSS) for blackwater where each effluent of the treatment can be used for one another. Furtheremore, an initial cost of the designed port-based discharge water treatment plant is conducted, resulting in total of IDR 22,487,086,876. The payback period (PBP) of the plant is 4 years.